Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/tox.23036
|View full text |Cite
|
Sign up to set email alerts
|

DLX6‐AS1 accelerates cell proliferation through regulating miR‐497‐5p/SNCG pathway in prostate cancer

Abstract: Prostate cancer (PCa) has become the second leading cause of cancer‐related mortality in males worldwide. Although the long noncoding RNA DLX6‐AS1 has been recognized to be an oncogene in multiple cancers, the biological function and regulatory mechanism of DLX6‐AS1 in prostate cancer are still obscure. In the present study, we observed that DLX6‐AS1 was significantly upregulated in PCa tissues and cells. Knockdown of DLX6‐AS1 inhibited PCa progression by suppressing cell proliferation and accelerating cell ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Recent studies confirmed that DLX6-AS1 is highly expressed in prostate cancer tissues and cells and has an important role in the progression of prostate cancer (Refs 69, 70). It was found that DLX6-AS1 recruits DNA methyltransferase 1 (DNMT1) to like-acetylglucosaminyltransferase (LARGE) promoter and induces the methylation of LARGE promoter to down-regulate the expression of LARGE, which finally enhances the proliferation, invasion, and metastasis of prostate cancer cells (Ref.…”
Section: The Effect Of Dlx6-as1 On Urinary System Cancersmentioning
confidence: 86%
See 2 more Smart Citations
“…Recent studies confirmed that DLX6-AS1 is highly expressed in prostate cancer tissues and cells and has an important role in the progression of prostate cancer (Refs 69, 70). It was found that DLX6-AS1 recruits DNA methyltransferase 1 (DNMT1) to like-acetylglucosaminyltransferase (LARGE) promoter and induces the methylation of LARGE promoter to down-regulate the expression of LARGE, which finally enhances the proliferation, invasion, and metastasis of prostate cancer cells (Ref.…”
Section: The Effect Of Dlx6-as1 On Urinary System Cancersmentioning
confidence: 86%
“…It was also identified that lncRNA DLX6-AS1 acts as a ceRNA of miR-497-5p and promotes the proliferation of prostate cancer cells and tumours through modulating the downstream target gene of miR-497-5p, synuclein gamma (SNCG), in vitro and in vivo (Ref. 70).…”
Section: The Effect Of Dlx6-as1 On Urinary System Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA DLX6-AS1 plays key regulatory roles in regulating tumorigenesis and progress via many mechanisms. One of the most important mechanisms is formation of lncRNA DLX6-AS1-miRNAs-mRNAs ceRNAs regulatory networks, in which lncRNA DLX6-AS1 serves as an endogenous competing RNA to competitively sponge miRNAs to further up-regulate the downstream target genes (mRNAs) of miRNAs ( Zeng et al, 2017 ; Zhang et al, 2017 ; An et al, 2018 ; Zhangmou et al, 2018 ; Li X. et al, 2019 ; Yang Q. et al, 2019 ; Zhang H. Y. et al, 2019 ; Li D. et al, 2019 ; Yang J. et al, 2019 ; Zhang N. et al, 2019 ; Fang et al, 2019 ; Huang et al, 2019 ; Lei et al, 2019 ; Sun et al, 2019 ; Wang et al, 2019 ; Zhao et al, 2019 ; Liu Y. et al, 2020 ; Du et al, 2020 ; Hu et al, 2020 ; Jia et al, 2020 ; Kong et al, 2020 ; Kong and Zhang, 2020 ; Liang et al, 2020 ; Qian et al, 2020 ; Wang et al, 2020 ; Xie et al, 2020 ; Yang et al, 2020 ; Liu et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ; Zhao et al, 2021 ; Zheng et al, 2021 ; Zhu et al, 2021 ). Xue et al (2021) and Feng et al (2021) also reviewed the regulatory roles serving as a ceRNA in various tumors which influence the prognosis of patients and which may be the therapeutic and prognosis target in malignant tumors.…”
Section: Lncrna Dlx6-as1 In Tumorsmentioning
confidence: 99%
“…8 To date, several lncRNAs have been defined as PCa specific. 9 Nevertheless, investigation of the function and mechanism of novel lncRNAs is necessary to find functional biomarkers in PCa progression. RHPN1-AS1 is a lncRNA that was differentially expressed in PCa patients and the potential function of RHPN1-AS1 in multiple tumor progression has been reported.…”
mentioning
confidence: 99%